Agostinho da Silva, personificação do intelectual português - Real, Miguel (2007)
Agostinho da Silva's life and work synthesize, in the second part of the twentieth century, one of the two deepest streams of Portuguese culture. Bom in política! opposition, Portuguese intellectuals were divided in two groups: 1 -the self interiorization group, of intellectuals living in isolation in the countryside, enjoying an aurea mediocritas, who have created a great work to be recovered by future generations; 2 -the most active intel- lectuals, living in exile, suffering because of their motherland's decadence, who designed a future salvation for their nation through the reviva! of great historical moments, as did Agostinho da Silva.